2015
DOI: 10.1017/s1049096515000281
|View full text |Cite
|
Sign up to set email alerts
|

Lights, Camera, Learn: Understanding the Role of Lecture Capture in Undergraduate Education

Abstract: Lecture-capture software allows instructors to record their class presentations for students to review as necessary. Although this technology has long been considered too expensive for large-scale use, it is quickly becoming ubiquitous and deployable using ordinary computers and consumer-grade software. Using survey and fi nal-grade data from a three-semester trial in a large introductory-level political science course, the authors demonstrate students almost universally approve of the technology and support i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Unfortunately, these authors did not assess the impact of lecture capture viewing on grades, whilst controlling for previous grades of the different cohorts or attendance. Indeed, Mallinson and Baumann (2015), drawing on self-reported data, found that a positive association between lecture capture usage and attainment drops away when attendance is controlled for. We similarly propose that whilst a positive link may exist between objective records of lecture capture usage and attainment, this will be reduced when we account for attendance and general academic ability.…”
Section: Impact Of Lecture Capture On Academic Attainmentmentioning
confidence: 99%
“…Unfortunately, these authors did not assess the impact of lecture capture viewing on grades, whilst controlling for previous grades of the different cohorts or attendance. Indeed, Mallinson and Baumann (2015), drawing on self-reported data, found that a positive association between lecture capture usage and attainment drops away when attendance is controlled for. We similarly propose that whilst a positive link may exist between objective records of lecture capture usage and attainment, this will be reduced when we account for attendance and general academic ability.…”
Section: Impact Of Lecture Capture On Academic Attainmentmentioning
confidence: 99%
“…They use recordings to revisit and clarify complex confusing topics (e.g., Elliot & Neal, 2016, Yeung et al, 2016, to prepare for exams (e.g. Chen & Lin, 2012;Copley, 2007;Mallinson & Baumann, 2015;von Konsky et al, 2009), and to learn at their own pace (e.g., Cooke et al, 2011;Euzent, Martin, Moskal, & Moskal, 2011;Tarr et al, 2015). While Scutter, Stupans, Sawyer and King.…”
Section: Personalising the Learner Journeymentioning
confidence: 99%
“…Leadbeater, Shuttleworth, Couperthwaite, 2013;Nordmann et al, 2017;Shaw & Molnar, 2011, Taplin et al, 2014. There is evidence that in addition to making greater use of recorded materials, second language learners show different patterns of usage, for example, being more likely to review materials directly after the lecture than other students (e.g., Mallinson & Baumann, 2015). The value of recordings for second language learners is exemplified in the following quote from Collier-Reed, Case, and Stott (2011,) "Sometimes the lecturer is talking to 100 students and you feel left out but when you listen to the podcast it is literally like a one to-one situation with the lecturer as well which is better.…”
Section: Personalising the Learner Journeymentioning
confidence: 99%
“…This is perhaps unsurprising as lecture capture tends to polarise views. Some consider it a priceless adjunct to promote inclusive education ( Blessinger et al, 2018 ; Mallinson & Baumann, 2015 ) whereas others view it as a perfect recipe for non-attendance ( Aldamen et al, 2015 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Drouin (2014) further revealed that even though students had a positive attitude toward lecture capture, they seldom viewed the actual lecture recordings. In addition, despite the general proclivity of the scholarly community to report only significant results and under-report those that are non-significant ( Kerr, 1998 ; Yukhymenko, 2011 ), it is telling that several works have indicated a non-significant association between lecture capture viewing and academic performance ( Bollmeier et al, 2010 ; Chapin, 2018 ; Euzent et al, 2011 ; Ford et al, 2012 ; Hadgu et al, 2016 ; Leadbeater et al, 2013 ; Mallinson & Baumann, 2015 ; Sarsfield & Conway, 2018 ; Traphagan et al, 2010 ).…”
Section: Findings and Discussionmentioning
confidence: 99%